Rational Cathode Design for High‐Power Sodium‐Metal Chloride Batteries. (15th August 2021) - Graeber, Gustav; Landmann, Daniel; Svaluto‐Ferro, Enea; Vagliani, Fabrizio; Basso, Diego; Turconi, Alberto; Heinz, Meike V. F.; Battaglia, Corsin
Abstract: The transition from fossil fuels to renewable energy sources requires economic, high‐performance electrochemical energy storage. High‐temperature sodium‐metal chloride batteries combine long cycle and calendar life, with high specific energy, no self‐discharge, and minimum maintenance requirements, while employing abundant raw materials. However, large‐scale deployment in mobility and stationary storage applications is currently hindered by high production cost of the complex, commercial tubular cells and limited rate capability. The present study introduces sodium‐metal chloride cells with a simple, planar architecture that provide high specific power while maintaining the inherent high specific energy. Rational cathode design, considering critical transport processes and the effect of cathode composition on the cell resistance, enables the development of high‐performance cells with average discharge power of 1022 W kg −1 and discharge energy per cycle of 258 Wh kg −1 on cathode composite level, shown over 140 cycles at an areal capacity of 50 mAh cm −2 . This corresponds to a 3.2C discharge over 80% of full charge. Compared to the best performing planar sodium‐metal chloride cells with similar cycling stability and mass loading in the literature, the presented performance represents an increase in specific power by more than a factor of four, while also raising the specific energy by 74%. Abstract : A mechanistic understanding of critical electrochemical and transport processes in sodium‐metal chloride batteries enables the rational design of the rate‐limiting cathode. Thus, both specific power and specific energy can be drastically increased, setting new performance standards for the highly promising sodium‐metal chloride technology.